2020
DOI: 10.1128/aac.00275-20
|View full text |Cite
|
Sign up to set email alerts
|

Anidulafungin and Micafungin Concentrations in Cerebrospinal Fluid and in Cerebral Cortex

Abstract: Anidulafungin and micafungin were quantified in cerebrospinal fluid (CSF) of critically ill adults and in cerebral cortex of deceased patients. In CSF, anidulafungin levels (<0.01 to 0.66 μg/ml) and micafungin levels (<0.01 to 0.16 μg/ml) were lower than those in plasma concentrations (0.77 to 5.07 and 1.21 to 8.70 μg/ml, respectively) drawn simultaneously. In cerebral cortex, anidulafungin and micafungin levels were 0.21 to 2.34 and 0.18 to 2.88 μg/g, respectively. Thus, MIC values of several pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In brain samples taken from our study population we had measured anidulafungin concentrations of 0.21 -2.34 µg/g and micafungin concentrations of 0.18 -2.88 µg/g. These data have been reported previously together with concentrations in cerebrospinal fluid of critically ill patients, which were even lower than brain concentrations (8). Preclinical studies revealed anidulafungin and micafungin tissue concentrations and distribution comparable with our findings, but in rodents, highest concentrations were measured in lung (11,(14)(15)(16).…”
Section: Invasive Candidiasis May Affect Various Tissues Causing Deep-seated Candidiasissupporting
confidence: 92%
See 2 more Smart Citations
“…In brain samples taken from our study population we had measured anidulafungin concentrations of 0.21 -2.34 µg/g and micafungin concentrations of 0.18 -2.88 µg/g. These data have been reported previously together with concentrations in cerebrospinal fluid of critically ill patients, which were even lower than brain concentrations (8). Preclinical studies revealed anidulafungin and micafungin tissue concentrations and distribution comparable with our findings, but in rodents, highest concentrations were measured in lung (11,(14)(15)(16).…”
Section: Invasive Candidiasis May Affect Various Tissues Causing Deep-seated Candidiasissupporting
confidence: 92%
“…Anidulafungin and micafungin concentrations were quantified in thyroid, lung, myocardium, spleen, liver, kidney, pancreas, and skeletal muscle. The echinocandins were extracted and quantified as described previously for brain (8). In brief, 0.2 g of tissue were homogenized with acetonitrile and methanol and concentrations were measured with high-performance liquid chromatography and UV detection (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, combination therapy should be utilized in specific settings such as those with (1) high azoleresistance rates [94] (2) in cases with lacking response to monotherapy (3) when the species of Aspergillus is unknown or susceptibility testing is pending (4) or when therapeutic level of voriconazole cannot be reached due to poor metabolism by concurrently administered medication. For CNS infections, combination therapy may be complicated due to concerns about antagonism between voriconazole and LAmB and the poor brain and cerebro-spinal fluid penetration of echinocandins [34,95]. The antimetabolite flucytosine is another option, particularly in combination with LAmB for severe Cryptococcal infections (meningitis, pneumonia), difficult to treat invasive Candida infections, as well as for urogenital infections involving fluconazole-resistant C. glabrata [96].…”
Section: Combination Therapymentioning
confidence: 99%
“…For certain infections, liposomal amphotericin B is preferred, such as when C. auris is isolated from the cerebrospinal fluid and reliable concentrations of echinocandins cannot be attained in that space. 83 …”
Section: Diagnosis and Treatmentmentioning
confidence: 99%